Plant water status, canopy temperature and chlorophyll fluorescence in relation to yield improvement in chickpea (Cicer arietinum L.) under soil moisture stress environments - SUMMY; K.D. SHARMA; K.S. BOORA; NEERAJ KUMAR (Journal of Agrometeorology, 2015)
The chickpea genotypes alongwith F4 progeny lines differing in their behavior towards drought stress were evaluated for seed yield, yield attributes and physiological traits related to drought tolerance. Parental genotypes, HC 1 and ICC 4958 were grown under both irrigated and drought conditions and progenies were grown under drought conditions only. Plant water status, relative stress injury (RSI), canopy temperature depression (CTD) and chlorophyll fluorescence (Fv/Fm) were measured at 50% flowering stage under drought conditions. Drought stress decreased the leaf water potential (LWP), leaf osmotic potential (LOP) and relative water content (RWC) in the plants. The water potential, osmotic potential, relative water content and relative stress injury in HC 1 were -1.20 MPa, -1.31 MPa, 59.2% and 31.28% respectively and in ICC 4958 were -1.00 MPa, -1.74 MPa, 66.58% and 20.93% respectively, under drought condition. Increase in CTD was 0.9 0C in ICC 4958 as compared to 2.06 0C in HC 1. The ICC 4958 maintained higher Fv/Fm ratio than HC 1 in both irrigated and drought conditions. There is a significant positive correlation between water potential, osmotic potential and RWC with seed yield, whereas, RSI and seed yield were negatively correlated. CTD has a significant negative correlation with WP, OP, RWC and seed yield. The seed yield of HC 1 and ICC 4958 were decreased under drought condition but decrease in yield of genotype ICC 4958 (24.96%) was less than genotype HC 1 (37.32%).